2017
DOI: 10.1016/j.celrep.2017.03.046
|View full text |Cite
|
Sign up to set email alerts
|

IGF1 Shapes Macrophage Activation in Response to Immunometabolic Challenge

Abstract: SUMMARY In concert with their phagocytic activity, macrophages are thought to regulate the host immunometabolic responses primarily via their ability to produce specific cytokines and metabolites. Here we show that IL-4 differentiated M2-like macrophages secrete IGF1, a hormone previously thought to be exclusively produced from liver. Ablation of IGF1 receptor from myeloid cells reduced phagocytosis, increased macrophages in adipose tissue, elevated adiposity, lowered energy expenditure and led to insulin-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(139 citation statements)
references
References 48 publications
7
128
1
Order By: Relevance
“…WAT is also innervated, although to a lesser degree, suggesting that alternative pathways participate in the regulation of Ucp1 expression in WAT. Recent investigations suggested that alternatively activated macrophages also contribute to BAT thermogenesis and browning of WAT by acting as a local source of catecholamines (14)(15)(16)(17), but these are in contrast with other recent findings (18,19). Here, we have demonstrated that ATMs express all enzymes necessary for catecholamine synthesis.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…WAT is also innervated, although to a lesser degree, suggesting that alternative pathways participate in the regulation of Ucp1 expression in WAT. Recent investigations suggested that alternatively activated macrophages also contribute to BAT thermogenesis and browning of WAT by acting as a local source of catecholamines (14)(15)(16)(17), but these are in contrast with other recent findings (18,19). Here, we have demonstrated that ATMs express all enzymes necessary for catecholamine synthesis.…”
Section: Discussioncontrasting
confidence: 71%
“…Recent insights have suggested that alternatively activated macrophages in adipose tissue act as a source of catecholamines, contributing to adaptive thermogenesis and browning of WAT (14)(15)(16)(17). However, the latest investigations have questioned this proposition (18,19). Thus, understanding the mechanisms involved in the development of functional beige cells is a key element in finding novel therapeutic targets for tackling obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, type 2 innate lymphoid cells (ILC2s) promote the differentiation of beige adipocytes from adipocyte precursors (Brestoff et al, 2015; Lee et al, 2015) to protect against diet-induced insulin resistance (Molofsky et al, 2013). Alternatively activated macrophages have been proposed to promote adaptive thermogenesis directly via their production of catecholamines (Nguyen et al, 2011), although independent studies found that adipose tissue macrophages from cold-exposed mice do not express the key catecholamine synthesis enzyme tyrosine hydroxylase (TH) (Chang et al, 2016; Fischer et al, 2017; Spadaro et al, 2017), and TH deletion in hematopoietic cells neither affected adipose tissue browning nor energy expenditure in response to cold (Fischer et al, 2017). In contrast, polarization towards a more proinflammatory activation directly inhibits adipose tissue browning (Chung et al, 2017) and in turn, browning has been described to limit adipose tissue inflammation (Cohen et al, 2014).…”
Section: Innate Immune Cellular Mediators Of Inflammationmentioning
confidence: 99%
“…By contrast, CM4 expressed many genes associated with alternatively activated macrophages, including CD163 and SLC40A1 (ferroportin), which control iron homeostasis 13 . CM4 also abundantly expressed IGF1 and DAB2, both drivers of the alternatively activated phenotype 14,15 and folate receptor beta (FOLR2), a receptor expressed . CC-BY-NC-ND 4.0 International license It is made available under a was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Classification and Annotation Of Myeloid Cell Clusters Reveamentioning
confidence: 99%